2008
DOI: 10.1016/j.visres.2007.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Target selection in visual search as revealed by movement trajectories

Abstract: We examined target selection for visually guided reaching movements in visual search, in which participants reached to an odd-colored target presented with two homogenous distractors. The colors of the target and distractors were randomly switched for each trial between red and green, and the location of the target was varied. Therefore either color could be a distractor or target, and the identity was resolved by grouping two distractors having the same color. Thus, there was ongoing competition between a tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
141
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(164 citation statements)
references
References 60 publications
20
141
3
Order By: Relevance
“…Regardless of whether rotation was required, during the first half of the reach action, an incongruent object in working memory slowed forward progress and attracted the hand toward the competing response element. The latter result converges nicely with previous demonstrations showing analogous effects for both hand and eye movements in two dimensions (McSorley et al, 2004;Song & Nakayama, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Regardless of whether rotation was required, during the first half of the reach action, an incongruent object in working memory slowed forward progress and attracted the hand toward the competing response element. The latter result converges nicely with previous demonstrations showing analogous effects for both hand and eye movements in two dimensions (McSorley et al, 2004;Song & Nakayama, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…The temporal parameters in both tasks were equally influenced by variables known to influence search times, such as the feature contrast between target and distractors, repetition of the same target dimension, or cuing of the upcoming target dimension. Similarly, Song and Nakayama (2008) observed that spatial parameters of a reaching movement were influenced by the same perceptual competition mechanisms as buttonpresses. When participants were asked to touch the odd-colored item in a search display, the trajectories of the reaching movements often deviated toward the distractors when the visual search task was difficult because there were only a few distractors (Song & Nakayama, 2006.…”
Section: Discussionmentioning
confidence: 87%
“…In several recent studies, researchers have analyzed the trajectory of a participant's response when selecting the answer with the touch of a finger (Boulenger et al, 2006;Finkbeiner, Song, Nakayama, & Caramazza, 2008;Schmidt & Seydell, 2008;Song & Nakayama, 2008a, 2008b, a saccade (Smit & Gisbergen, 1990) or a computer mouse (Freeman & Ambady, 2009;Spivey, Grosjean & Knoblich, 2005). The response choices are presented at different locations in space so that an in-flight deviation toward the competing, incorrect answer can be revealed.…”
mentioning
confidence: 99%